OPTIMASI PENGEMBANGAN DIRI DOSEN DALAM MENYIAPKAN SDM DI ERA MEA - Ari Muhardono; Chalimah Chalimah (Jurnal Ekonomi Dan Bisnis, 2017)
Along with the development of global market demands, higher education institutions must also continue to make creativity and innovation  so that the quality of learning increases,  so that the graduates produced  have a high competitiveness.  To  realize  the  human  resources  that  have  competitiveness  required  the  development  of  self- lecturers. Many  factors can affect the self-development  of  lecturers. This study  was conducted  with the aim  to analyze the influence of work ethic and commitment  to self -development  of lecturers  at Pekalongan  Univ ersity (Unikal).  In  this  study,  the  use  of  work  ethic  variables  and  commitment  to  analyze  the  influence  of  self - development.  This research  uses multiple  regression  analysis  method.  Data  obtained  from questionnaires  that have been  inputted online by students  in academic information  system (SIAKAD)  and assessment  conducted  by Institute of Unique Quality  Assurance  (LPMU). The  results of this  study  indicate that  work ethic variables  and commitment   variables   together  significantly   influence   the  self -development   of   lecturers.   Low  learner   self- development  can be improved by encouraging work ethic variables and commitment  variables.